Kebersihan dalam Persepektif Hadis - Solihin, Solihin; Lisalam, Repa Hudan (STAI Denpasar Bali, 2025)
This study aims to discuss the hadith perspective on cleanliness. This research is a qualitative research using literature study to interpret the hadith about cleanliness with a content analysis approach. The results and discussion of this study include the notion of cleanliness, hadiths about cleanliness, and cleanliness from a hadith perspective. This study concluded that maintaining cleanliness is very important for daily life including physical and spiritual cleanliness and environmental cleanliness. Learning It is suggested to all parties to maintain cleanliness which is not only related to ethics but also religious values, especially the importance of implementing clean living habits from an early age through the role of Islamic institutions.